2021
DOI: 10.1177/00220426211002125
|View full text |Cite
|
Sign up to set email alerts
|

Motivators for Cannabis Use Among Young Adults in Outpatient Psychiatric Care: A Qualitative Study

Abstract: Cannabis use is prevalent among youth with mental illness, despite the increased risk of exacerbating psychiatric symptoms. The rapidly changing legality of cannabis has contributed to its normalization and decreased perceived risks. This study qualitatively gathered young adult psychiatric patients’ ( n=15) perspectives on cannabis to inform a use reduction intervention. NVivo12 was used to organize coded data and facilitate analysis. Motivations to use included viewing cannabis utilization as normalized, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…I feel if I take the medications I'll just progressively change and not be myself.(Whiteley et al, 2021)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…I feel if I take the medications I'll just progressively change and not be myself.(Whiteley et al, 2021)…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative studies (Bizzarri et al, 2007; Bolton et al, 2009; Lorberg et al, 2010; Meyer et al, 2012; Sonne et al, 1994; Tyler et al, 2015; Weiss, 2004; Weiss et al, 1992) used a variety of self‐report measures (see Table 1). The qualitative studies (Brown & Stewart, 2008; Canham et al, 2018; Castaneda, 2020; Cornford et al, 2012; Healey et al, 2009; Newman et al, 2012; Ward, 2011; Whiteley et al, 2021) mostly used qualitative interviews combined with thematic analysis. The two case series papers (Grinspoon & Bkalar, 1998; Gruber et al, 1996) reported on 7 and 5 cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in cannabis legalization policies have contributed to the normalization of cannabis use, especially among young adults ( Hughes et al, 2015 ). Young adults often perceive cannabis as “natural” and less harmful than other substances; yet it can adversely affect brain function, particularly during the critical developmental stage of young adulthood ( Whiteley et al, 2021 ). Medical cannabis is currently legal in 38 states, four US territories, and the federal District of Columbia (DC); non-medical use is permitted in 23 states, three US territories, and DC ( McClure et al, 2023 , National Conference of State Legislatures, 2023 ).…”
Section: Introductionmentioning
confidence: 99%